Evaluation of the effect of co-transplantation of collagen-hydroxyapatite bio-scaffold containing nanolycopene and human endometrial mesenchymal stem cell derived exosomes to regenerate bone in rat critical size calvarial defect - Masoumeh Einabadi; Azadeh Izadyari Aghmiuni; Laleh Foroutani; Arman Ai; Mojdeh Salehi Namini; Ali Farzin; Amir Nahanmoghadam; Sadegh Shirian; Hossein Kargar Jahromi; Jafar Ai (Regenerative Therapy)
This study aimed to evaluate the effect of nanoparticles based on the PLGA and biomolecule of lycopene (i.e. NLcp) and exosomes loaded on hydroxyapatite/collagen-based scaffolds (HA/Coll), on human endometrial MSCs (hEnMSCs) differentiation into osteoblast cells. To this end, after synthesizing NLcp and isolating hEnMSC-derived exosomes, and studying their characterizations, HA/Coll scaffold with/without NLcp and exosome was fabricated. In following, the rat skull-defect model was created on 54 male Sprague–Dawley rats (12 weeks old) which were classified into 6 groups [control group (4 healthy rats), negative control group: bone defect without grafting (10 rats), and experimental groups including bone defect grafted with HA/Coll scaffold (10 rats), HA/Coll/NLcp scaffold (10 rats), HA/Coll scaffold + exosome (10 rats), and HA/Coll-NLcp scaffold + exosome (10 rats)]. Finally, the grafted membrane along with its surrounding tissues was removed at 90 days after surgery, to assess the amount of defect repair by Hematoxylin and eosin staining. Moreover, immunohistochemical and X-ray Micro-Computed Tomography (Micro-CT) analyses were performed to assess osteocalcin and mean bone volume fraction (BVF). Based on the results, although, the existence of the exosome in the scaffold network can significantly increase mean BVF compared to HA/Coll scaffold and HA/Coll-NLcp scaffold (2.25-fold and 1.5-fold, respectively). However, the combination of NLcp and exosome indicated more effect on mean BVF; so that the HA/Coll-NLcp scaffold + exosome led to a 15.95 % increase in mean BVF than the HA/Coll scaffold + exosome. Hence, synthesized NLcp in this study can act as a suitable bioactive to stimulate the osteogenic, promotion of cell proliferation and its differentiation when used in the polymer scaffold structure or loaded into polymeric carriers containing the exosome.